Induced Oxidation of Glycine by Fe(II) - Farooqui, Mazahar; Zaher, Ahmed; Mohd. Arif Kkan, Pathan; Ubale, Milind; Ubale, Sanjay (Asian Journal of Chemistry, 2010)
The present paper deals with induced oxidation of glycine by Fe(II). The probable mechanism suggests the involvement of Mn(III) as an intermediate species. Presence of salts like potassium nitrate or lanthanum(III) nitrate decreases the induction factor of the reaction.